Granulomatous fat necrosis of breast a diagnostic dilemma: a rare case report - Mukesh, Aswin; A., Murugan; K. V., Rajan (International Surgery Journal, 2022)
Fat necrosis in breast is a rare benign condition, which can mimic carcinoma and Tuberculosis (TB) of breast in both clinical and radiological assessment. Histopathology in such cases may distinguish granulomatous lesion from carcinoma, however granulomas are identified in both fat necrosis and tuberculosis which is difficult to differentiate. Fat necrosis in breast is often not associated with axillary lymph nodes, which can differentiate fat necrosis from tuberculosis and breast carcinoma. But high index of suspicion is always required. We hereby report a case of a 40-year old female, who presented with lump in the right breast which lead to diagnostic dilemma.